Pregnancy after unilateral operation an androblasicuna - Mochamad Anwar Mochamad Anwar (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1992)
Androblastoma is a rare semimalignant ovarian tumor which occurs most frequently during the reproductive years and is assumed to arise from sexually ambivalent cells noted in the ovary of the 6-7 weeks embryo or to be of teratoid origin. The excessive secretion of testosteron will occur and lead to masculinism, while androgens will suppress normal ovarian function and cause the sign of virilization. A 3-years subferdIc case was a 27 year-old-woman with typical syndrome of androblastoma manifested by virilization and defeminization. The testosteron concentration was 700 ng/dl, prolactin: 8,4 p.g/1, Barr body drumstick (+), while the chromosomal analysis indicated female genotype (46 XX). Simple oophorcctomy was done, the size of the left ovarian tumor was 9 x 7 x 8 cm, encapsulated and there was no adhesion. The uterus and adnexa were normal. The pathological result was malignant. Alkeran cytostatic treatment was given in 5 series of 12,5 mg orally. However, the pregnancy occurred during the treatment. The patient was then managed carefully as a routine procedure without and-cancer drugs anymore. The baby was born normally without any congenital anomaly. The signs of either virilism or masculinism decreased. Hormonal examination showed a normal level of testosteron.Key Words: infertility - androblastoma - cytostatics - ovarian tumor - virilization